1971
DOI: 10.1071/bi9710275
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in the Late Larva of Calliphora Stygia Iii. The Occurrence and Synthesis of Specific Tissue Proteins

Abstract: The occurrence and synthesis of soluble proteins from certain larval tissues of O. 8tygia have been examined by acrylamide.gel electrophoresis and autoradiography at the feeding (days 4-6), wandering (days 7-10), and quiescent (day 11) stages of third-instar development. The protein species investigated are distributed as follows: fat body, 22; plasma, 21; body wall, 18; salivary gland cells, 16; salivary secretion, 18.The predominant soluble proteins of fat body, body wall, and salivary gland cells are in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1971
1971
1989
1989

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The bulk ofthe increase in fat body protein which occurs between days 7 and 11 oflarval development is due to an increase in the proteins of bands FI5-19, and, at the quiescent stage, to bands F4-1O also (Kinnear, Martin, and Thomson 1971). The fat body protein spectrum of third-ins tar larvae is qualitatively similar (Kinnear, Martin, and Thomson 1971) during the period from day 4 to day 11, which includes both feeding and wandering stages.…”
Section: (C) Relationship Of Plasma and Fat Body Proteinsmentioning
confidence: 48%
See 4 more Smart Citations
“…The bulk ofthe increase in fat body protein which occurs between days 7 and 11 oflarval development is due to an increase in the proteins of bands FI5-19, and, at the quiescent stage, to bands F4-1O also (Kinnear, Martin, and Thomson 1971). The fat body protein spectrum of third-ins tar larvae is qualitatively similar (Kinnear, Martin, and Thomson 1971) during the period from day 4 to day 11, which includes both feeding and wandering stages.…”
Section: (C) Relationship Of Plasma and Fat Body Proteinsmentioning
confidence: 48%
“…2(b)] revealed that radioactivity was present in fat body bands F15-19. These are electrophoretically comparable with plasma proteins H15-19, except that the fat body contains no band corresponding to the slower of the two overlapping components of H15 (Kinnear, Martin, and Thomson 1971). There was no apparent radioactivity at the positions of bands H4, 11, 20, or 21.…”
Section: (B) Protein Species Involved In Uptake By Fat Bodymentioning
confidence: 50%
See 3 more Smart Citations